Locational Pattern of Brothel-Based Commercial Sex Works In Kaduna Metropolis of Kaduna State, Nigeria - JOEL, AJIBUAH BOLANLE (2013)
Commercial sex work is a profession as old as human existence. It is driven by causes and implications, but very little or no examination ever conducted on its locality in our society, perhaps this is based on pretentious nonexistence. This paper investigates the spatial location of brothels and socioeconomic susceptibility of commercial sex workers in Kaduna Metropolis. Over 400 semi-structure questionnaires were administered principally to female commercial sex workers in 47 identified brothels. Key informant interviews were also conducted among duty-bearers and change agents. The data were analyzed using correlation analysis of ANOVA and qualitative descriptive techniques for presentation of findings. The study reveals asymmetric locational pattern of brothels towards the southern part of the Metropolis especially where Christian religion is dominant and unprecedented young adult female involvement with socio- economic issues facilitating their predisposition into the profession. For the trade to be nipped from the bud there is need for resuscitation of religion values and moral decorum, strict adherent to religious teaching, and pragmatic campaign on the health implication with particular reference to the proliferation and vulnerability of people to HIV/AIDs and other vector disease